3D structure and evolution of an extensional fault network of the eastern Dampier Sub-basin, North West Shelf of Australia. (March 2020) - Deng, Hongdan; McClay, Ken; Bilal, Awad
Abstract: Insights of spatial and temporal development of fault network in 3D is crucial for understanding the process evolution of complex fault network and for evaluating the regional and local stresses control on structure development. We demonstrate a fault network on the eastern Dampier Sub-basin, North West Shelf of Australia, which consists of (1) a ENE-trending fault array that has a through-going segment at depth and a series of left-stepping fault splays at upper levels, and (2) a network of ENE- and NNE-trending intersecting faults decoupled from the basement structures. This research shows that the segmented ENE-trending fault array developed through three extensional phases in the Late Paleozoic, in the Early Jurassic, and in the Late Middle Jurassic. Fault analysis shows that the summed displacement of the segmented, en échelon faults behaves as a single fault and that the basement fault controlled the fault array in the upper section through vertical linkages– a typical coherent fault system. The NNE- and ENE-trending intersecting faults formed simultaneously in the Late Middle Jurassic; as such, they might have controlled by 3D strain field released from the Rosemary and Mermaid fault systems bounding the fault network. This implies that fault geometry derived from 3D seismic interpretation need to be treated with caution as the alignment of fault sets may not directly relate to regional, far-field stress but, in some cases, significantly modified by local stresses induced by reactivated larger faults. This study provides an analogue for the interpretation of other rift systems, where structures were controlled by competing forces of regional and local stresses and where reactivated and newly-formed structures coexist in polyphase of extensions. Highlights: A complex network of faults including fault array and intersecting faults were demonstrated in 3D. The fault array developed through three stages of extension and were reactivated from basement fault at depth; the intersecting faults developed simultaneously and demonstrate mutual intersecting relationship. A 3D (triaxial) strain field is proposed to explain the development of these complex faults that formed in response to local stresses imposed by the interplay of larger bounding fault systems. This study provides an analogue for the interpretation of rift systems, where structures were controlled by competing forces of regional and local stresses and where reactivated and newly-formed structures coexist in polyphase of extensions.